The STAR PXL detector. (22nd December 2016) - Contin, G.
Abstract: The PiXeL detector (PXL) of the STAR experiment at RHIC is the first application of the state-of-the-art thin Monolithic Active Pixel Sensors (MAPS) technology in a collider environment. Designed to extend the STAR measurement capabilities in the heavy flavor domain, it took data in Au+Au collisions, p+p and p+Au collisions at 0√ s NN =20 GeV at RHIC, during the period 2014–2016. The PXL detector is based on 50 μ m-thin MAPS sensors with a pitch of 20.7 μ m. Each sensor includes an array of nearly 1 million pixels, read out in rolling shutter mode in 185.6 μ s. The 170 mW/cm 2 power dissipation allows for air cooling and contributes to reduce the global material budget to 0.4% radiation length on the innermost layer. Experience and lessons learned from construction and operations will be presented in this paper. Detector performance and results from 2014 Au+Au data analysis, demonstrating the STAR capabilities of charm reconstruction, will be shown.